The (de)construction of culture in interpreter-mediated medical discourse - Felberg, Tatjana R.; Skaaden, Hanne (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
In Norway, perceived communication problems in medical encounters with minority patients are often ascribed to ‘culture’ by the professional in charge of the institutional dialogue. Even in literature on medical encounters involving language barriers and interpreting, culture is used as an explanatory tool for observed complications, and an expansion of the interpreter role is suggested as the remedy. Comparing statements about the concept ‘culture’ made by medical professionals against a backdrop of Norwegian legislative texts on the role of the medical professional and interpreter, this article deconstructs culture as an explanatory tool. It is suggested that the source of the perceived problems of communication may lie at general levels of human interaction, e.g. concentration or language proficiency, rather than culture. We argue that the use of the concept of culture may lead to ‘othering’ of minority patients, may conceal rather than reveal communication problems, and may confuse the intersection between interpreters’ and medical professionals’ areas of expertise. Ultimately, not only minority patients’ health but also medical personnel’s professional integrity may be threatened.